The problem of correction of combined cardiac and metabolic disorders in the format of restorative medicine specialization - L. G. Agasarov; O. Yu. Kirgizova; V. K. Frolkov; T. V. Konchugova; T. V. Apkhanova (Лечащий Врач)
The paper is devoted to the evaluation of therapeutic possibilities of pharmacopuncture (stimulation of reflexotherapy points by injection of drugs) in case of combined cardiac and metabolic disorders.